Peri-conceptional supplementation of folic acid-knowledge and practices of pregnant women and health providers - Vartika Saxena (Journal of Family Medicine and Primary Care, 2016)
Context: Neural tube defects (NTDs) are one of the most common congenital anomalies. NTDs are preventable if folic acid (FA) is supplemented before and during conception. Knowledge and supplementation of FA by pregnant women as well as it's timely provision by health providers is crucial in reducing the burden of NTDs in the community. Aim: To study the knowledge and supplementation of FA by pregnant women and it's prescription/provision by health providers. Settings and Design: A cross-sectional study was conducted in the block Doiwala, District Dehradun, Uttarakhand. Subjects and Methods: A total of 400 pregnant women and 121 government health providers (5 medical officers, 25 auxiliary nurse midwives [ANMs], and 91 accredited social health activists [ASHAs]) were interviewed on predesigned, pretested questionnaire by study/field investigator. Statistical Analysis Used: Proportion of different variables calculated and Chi-square test with Yates correction was applied. Results: Of 400, 73.50% of women had heard of FA. Overall, knowledge scores suggested intermediate to low level of knowledge about FA. Totally 94.25% of women had planned pregnancies; however, only 4.75% of women reported FA supplementation before conception. This indicates that if these women would have been properly counseled and prescribed FA, they might have taken it. About 60% of medical officers, 4% of ANMs, and 3.3% of ASHAs knew FA deficiency as one of the causes of NTD. None of the health providers reported to be prescribing/counseling FA to pregnant women. FA was out of supply on the block at the time of the study. Conclusions: Knowledge and supplementation practices related with FA are poor.